Research of the Dynamic Characteristic of Space Symmetrical Development Mechanism with Clearance Joint - Xupeng Wang; Geng Liu; Shangjun Ma; Ruiting Tong (Jixie chuandong)
In order to study the influence of clearance joints on dynamic characteristics of space symmetrical deployment mechanism, based on an improved nonlinear impact force model, an space symmetrical deployment mechanism is used as an example, and comparative analysis of the numerical simulation and results of deployment process under three conditions with different clearance joints (c=0.01 mm, 0.05 mm and 0.1 mm) are carried out. The simulation results indicated that with the effects of clearance, the impact force and center orbit of the journal and bearing in clearance joint appear clear vibration, and the larger clearance sizes, the more obvious deviation. Meanwhile, with the influence of clearance joints, the space development mechanism also appearance nonlinear phenomenon during development process, and the larger clearance size, the more obvious effects of driving load on the dynamic response of the mechanism, even lead the mechanism from stable state to non-linearity again.